Padrões de uso de Vá Lá e Vamos Lá na norma brasileira do português: micro-construções e gramaticalização - Teixeira, Ana Cláudia Machado (2010)
Our hypothesis is that lexical items of vá lá and vamos lá lose their autonomy and no longer express its original meaning, becoming a new and unique meaning in favor of communicative efficiency.The analysis investigates typological sequences that allow observe mechanisms linked to linguistic changes and related to the process of grammaticalization that provide the formation of constructions as said Goldberg (1995;2006) and Croft (2001) and micro-constructions as the Traugott said (2008a, forthcoming). Under the focus of the linguistic functionalism, according Givón (2001), Bybee (2003), Furtado da Cunha, Oliveira and Martelotta (2003),Traugott (2003 - 2008, forthcoming), and Traugott Dasher (2005), among others, we examined the patterns of constructions use can assume according to communicative situation and the influence of the syntactic-semantic structure for the grammaticalization in specific contexts. The process begins at the moment in which the speaker tends to encode their subjectivity in proposition by their attitudes and beliefs and follows through producer-recipient relationship, resulting in intersubjectivity when the focus moves to the listener. Thereafter, the trajectory of the constructions are abstractions by account of motivations in order metonymic and metaphorical, since pressures of contextual order allow reinterpretations. The occurrences in its original meaning living with their new directions show that polysemy is favored by inferences suggested the changes interactions. In vá lá the verb start of within concrete area of displacement in space for a shift in the more abstract expressivity and the locative, in a physical-space meaning of a place to a place in a opinion. On vamos lá, the verb is replaced by a more abstract domain of shift in intention and your locative to a place in opinion. The corpus is made by texts captured in magazines of the publishers: Brasileiros, Abril, Globo and the sites: D& G, PEUL / UFRJ, NURC-RJ/SP, Corpus do português.